The chances for a thorough reform of the common agricultural policy - Ulrich Koester (Intereconomics, 1981)
That the Common Agricultural Policy of the European Community is in need of reform is by now commonly accepted. But all moves for a reform on the political level have been postponed until after the French elections in the spring, a fact which highlights the political problems. Is there a real chance of a thorough reform of the CAP?
Keywords: 330; European Community